Financing Strategies of Startups - Mahin Rahimpour; Mahmood Yahyazadeh Far; Hassanali Aghajani; adel azar (مطالعات مدیریت راهبردی, 2021)
Nowadays with the emergence of a knowledge-based economy,innovative businesses are very important for countries due to their job and wealth creation and their competitiveness in the global economy. These businesses are always facing key challenges due to their different nature form common businesses of which one of the most important challenges is about their financing and raising capital. This study seeks to provide an interactive model for the life cycle ofinnovative start-ups and financing policies. For this purpose, according to the existing literature gap and theoretical contradictions, the present study was conducted using Grounded theory method. Data were generated based on 11 expert opinions as well as previous studies and were analyzed in open,axial, and selective coding steps. The findings showed that innovative start-ups have four key stages in financing, including seeds, start-ups, growth and development and Financing strategies included internal and external strategies generally, and most known internal strategy was bootstrapping and the most important external strategies were Euity Financing, debt-based financing, hybrid financing, grants, financial and tax incentives, and cryptocurrencies. . Causal variables finance start-up businesses include individual factors such as the founder's traits, and organizational factors such as information transparency, team members, ideas, Key Contextual Variables for financing start-up businesses include policy and legislation, technology platform, organizational platform, competitive platform, socio-cultural platform and educational platform, and for intervening factors university, industry, sanctions, talent migration, and competitors Were identified. Consequences fall into several categories: micro-consequences at the business level and macroeconomic Consequences such as social, and environmental consequences.